2022
DOI: 10.1186/s12915-022-01229-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide annotation of protein-coding genes in pig

Abstract: Background There is a need for functional genome-wide annotation of the protein-coding genes to get a deeper understanding of mammalian biology. Here, a new annotation strategy is introduced based on dimensionality reduction and density-based clustering of whole-body co-expression patterns. This strategy has been used to explore the gene expression landscape in pig, and we present a whole-body map of all protein-coding genes in all major pig tissues and organs. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Antibodies produced within the HPA project (see Supplementary Data 14 for antibody information) with high reliability (based on human antibody validation 112 , 113 ), and over 80% sequence homology to pig orthologs was used for immunostaining. All antibodies are published on the HPA portal ( www.proteinatlas.org ) with more details about antibody reliability and tissue distribution in humans Formalin-fixed paraffin-embedded (FFPE) pig tissues, previously validated and prepared 30 , was utilized for validating that scRNA-seq is a robust method for the classification of different cell types. The staining protocol follows our previous study by Karlsson et al, as briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies produced within the HPA project (see Supplementary Data 14 for antibody information) with high reliability (based on human antibody validation 112 , 113 ), and over 80% sequence homology to pig orthologs was used for immunostaining. All antibodies are published on the HPA portal ( www.proteinatlas.org ) with more details about antibody reliability and tissue distribution in humans Formalin-fixed paraffin-embedded (FFPE) pig tissues, previously validated and prepared 30 , was utilized for validating that scRNA-seq is a robust method for the classification of different cell types. The staining protocol follows our previous study by Karlsson et al, as briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the pig BodyMap atlas with the conventional bulk RNA-seq method has been reported 29 . Using similar bulk RNA-seq based transcriptome profiling, we have systematically profiled the protein-coding transcriptome in 98 pig tissues ( www.rnaatlas.org ) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Genes in this cluster were enriched for KEGG pathways including "steroid biosynthesis" (p = 1.91 × 10 -11 ), "aldosterone synthesis and secretion" (p = 7.10 × 10 -6 ), and "cortisol synthesis and secretion" (p = 1.46 × 10 -5 ) (Figure 4B). The expression of STAR and CYP11A1 in chicken adrenal glands differs from human, mouse, pig, and sheep, and is restricted to adrenal glands with specific high expression, in which the expression level of STAR was nearly 500-fold higher than that of ovarian tissue (Karlsson et al, 2022). Adrenal steroidogenesis is carried out by microsomal and mitochondrial enzymes, which are highly conserved among vertebrates (Castillo et al, 2015).…”
Section: The Adrenal Glandmentioning
confidence: 99%
“…Investigating region-specific gene expression can help to understand life processes and physiological functions. The region-specific transcriptomic analyses have been reported in many farm animals, for instance, water buffalo [ 17 ], sheep [ 18 ], pigs [ 19 ], cattle [ 20 ], which provide valuable insights into understanding the expression regulation involved with functional differences among regions. Our study identified a total of 80 RSGs in multiple beef cuts from different regions based on the previously described method [ 13 ].…”
Section: Discussionmentioning
confidence: 99%